Precipitation but not soil texture alters effectiveness of dicyandiamide to decrease nitrate leaching from dairy cow urine. (11th June 2014) - Shepherd, M.; Welten, B.; Wyatt, J.; Balvert, S.; Goss, Michael
Abstract This experiment compared the effectiveness of the nitrification inhibitor dicyandiamide (DCD) in decreasing NO3‐N leaching from dairy cow urine (1000 kg N/ha equivalent). DCD was applied to perennial ryegrass (Lolium perenne L.) and white clover (Trifolium repens L.) on three soil types (silt loam, sandy loam and clay) and under two precipitation regimes using intact soil monolith zero tension lysimeters (50 cm diameter by 65 cm deep). Over the two experiment years, annual precipitation (rainfall plus supplemented irrigation) covered the range 1103 to 2351 mm. Soil type affected the forms of N that leached after urine application. Most urea was lost from the clay soil in the first drainage collections after application. Ammonium‐N leached from the sandy soil. Apart from one soil type (sandy loam) giving a nil response to DCD in 1 yr, there was no strong evidence that soil type changed DCD effectiveness (the amount of NO3‐N retained, expressed as a percentage of the NO3‐N leached from untreated urine). Where DCD decreased leaching, effectiveness ranged between 6 and 57% with a mean value of 34 ± 5%. Drainage depth explained 50% of the variation in DCD effectiveness (P < 0.05) and indicated a 7% decrease per 100 mm extra drainage. Extra pasture growth and N uptake were strongly related to the amount of N saved by DCD application. We conclude that there may be scope to use rainfall/drainage as an estimate of likely DCD effectiveness at a site, but further work is required to test this across a wider range of circumstances.